2019
DOI: 10.1007/s00426-019-01193-3
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous future cognition: the past, present and future of an emerging topic

Abstract: In this Editorial, we discuss the past, present and future of an emerging and fast-developing field-spontaneous future cognition. In tracking the past of this research, the trajectories of research on mind-wandering, episodic future thinking and prospective memory are briefly examined, and their relation with spontaneous future cognition demarcated. Three broad methodological approaches (questionnaire, naturalistic and laboratory) used to study spontaneous future thoughts are described, providing an overview o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 146 publications
2
39
0
Order By: Relevance
“…Finally, it deserves mention that mental time travel can not only be initiated voluntarily but can also occur spontaneously (Berntsen, 2010(Berntsen, , 2019Christoff et al, 2016;Cole & Kvavilashvili, 2019;Smallwood & Schooler, 2015). Involuntary autobiographical memories and future thoughts are indeed common in everyday life (Berntsen & Jacobsen, 2008); when we are not entirely focused on a given task, personal goals, current concerns, and other autobiographical contents tend to spontaneously come to mind (Baird et al, 2011;Cole & Berntsen, 2016;Stawarczyk et al, 2011).…”
Section: Modes Of Mental Time Travelmentioning
confidence: 99%
“…Finally, it deserves mention that mental time travel can not only be initiated voluntarily but can also occur spontaneously (Berntsen, 2010(Berntsen, , 2019Christoff et al, 2016;Cole & Kvavilashvili, 2019;Smallwood & Schooler, 2015). Involuntary autobiographical memories and future thoughts are indeed common in everyday life (Berntsen & Jacobsen, 2008); when we are not entirely focused on a given task, personal goals, current concerns, and other autobiographical contents tend to spontaneously come to mind (Baird et al, 2011;Cole & Berntsen, 2016;Stawarczyk et al, 2011).…”
Section: Modes Of Mental Time Travelmentioning
confidence: 99%
“…Drawing upon recent work, spontaneous future thinking is characterised here as automatic, fast and undirected (see Table 2) (Berntsen & Jacobsen, 2008;Finnbogadottir & Berntsen, 2011;; for a definition, see Berntsen, 2019; Cole & Kvavilashvili, 2019). As stated at the beginning of this article, the key question in future thinking research concerns the paradox of having fully-fledged episodic future thoughts in the absence of wilful constructive processes.…”
Section: Spontaneous Future Thinkingmentioning
confidence: 99%
“…Based on these inclusion criteria, the review of studies on mind-wandering and spontaneous future thinking (see Table 1), a newly emerging field within research on episodic future thinking (Berntsen, 2019; Cole & Kvavilashvili, 2019, 2020), provided strong support for the pragmatic theory of prospection, which considers planning as the most important and frequent form of episodic future thinking in the service of accomplishing one’s immediate needs and goals (Baumeister et al, 2016; Baumeister et al, 2018; D’Argembeau, 2016). In addition, several studies on prospective memory showed that just thinking about such upcoming tasks and plans enhances the likelihood of them being carried out in the future (e.g., Kvavilashvili & Fisher, 2007).…”
mentioning
confidence: 99%